Soil water dynamics - Warrick, Arthur W. (Oxford University Press, 2003)
Symbols and Abbreviations. 1. The Soil System. 2. Soil Water Flow. 3. Saturated Flow. 4. One-Dimensional Absorption. 5. One-Dimensional Infiltration and Vertical Flow. 6. Multidimensional Water Flow in Variably Saturated Soils. 7. Solute and Contaminant Transport. References. Index.